An Exploratory Research on the Application of Lean Management Principles in the Pakistani Banking Industry - Jamali, Saifullah (2015)
Lean management can be simply described as a systematic way of reducing waste. Over the years, this philosophy has transgressed industry boundaries as more and more organizations outside the manufacturing world are implementing its different aspects to drive productivity improvements.The financial crisis faced by economies around the world has brought with it a hailstorm of problems for banks. Reduced spreads, increased competition and stricter regulatory controls are forcing these financial institutions to look towards new ways of improving operational efficiency. Thus in order to explore these new areas further, this research explores the applicability of lean management principles in the Pakistani banking sector. A detailed examination of the literature available on lean, its evolution and its adoption in the service sector was conducted to understand the applicability of lean in the service sector in general and then in the banking sector. Literature available on the various lean tools and techniques being applied in the banking sector around the world was also analyzed to develop a better understanding about its implementation. As not much research has been done on lean implementation in Banks operating in Pakistan, this paper follows an exploratory approach. The findings of the study include the common types of wastes present in banks, which can be related to the generic wastes present in service sector organizations. Furthermore, it was established that even though there was evidence of lean techniques being used in banks in Pakistan,these techniques were being implemented in an abstract way that only allows for short-term productivity improvements and the question of sustaining these benefits remains.